Decorative composition tasks for painting as a means to develop students' creative personality (direction "Design") - Berdiševs, Vladimirs; Zaharovs, Nikolajs; Kučerovskaja, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The essay is dedicated to the problems of teaching painting at Design faculties of high schools and universities. The main task both in painting is to teach students to make a conscious choice of visual tools. Selection of pictorial means shall be determined by a figurative idea and shall contribute to the most expressional solution of a set problem. Approach to painting changes to become more analytical one, based on the laws of formal composition and color science. Special attention is paid to seeking for figurative solutions. In addition to educational activities students are challenged to perform their works at a high professional and artistic level and to develop their creative personality. In painting students shall create decorative compositions in the most free form provided that image objects are recognizable. Understanding of form elicitation patterns or image creation principles contributes to a more precise choice of figurative instruments and allows developing students’ creative abilities as required by the specifics of their professional education. . Purpose of the article: studies of painting teaching experience for efficiency and quality improvement, evaluation of disciplines that provide fundamental artistic training in development of designing skills and abilities of students. The method is based on the studies of General Painting Department of St. Petersburg Academy of Applied Arts named after Stieglitz as well as on the analysis of teaching methods of Russian classic academic school, in particular by N. Volkov and P. Chistyakov. Traditional methods of pedagogical studies have been used such as examination/observation, experience analysis and pedagogical experiments.